Design study of beam transport lines for BioLEIR facility at CERN. (18th September 2017) - Ghithan, S.; Roy, G.; Schuh, S.
Abstract: The biomedical community has asked CERN to investigate the possibility to transform the Low Energy Ion Ring (LEIR) accelerator into a multidisciplinary, biomedical research facility (BioLEIR) that could provide ample, high-quality beams of a range of light ions suitable for clinically oriented, fundamental research on cell cultures and for radiation instrumentation development. The present LEIR machine uses fast beam extraction to the next accelerator in the chain, eventually leading to the Large Hadron Collider (LHC) . To provide beam for a biomedical research facility, a new slow extraction system must be installed. Two horizontal and one vertical experimental beamlines were designed for transporting the extracted beam to three experimental end-stations. The vertical beamline (pencil beam) was designed for a maximum energy of 75 MeV/u for low-energy radiobiological research, while the two horizontal beamlines could deliver up to 440 MeV/u. One horizontal beamline shall be used preferentially for biomedical experiments and shall provide pencil beam and a homogeneous broad beam, covering an area of 5 × 5 cm 2 with a beam homogeneity of ± 5%. The second horizontal beamline will have pencil beam only and is intended for hardware developments in the fields of (micro-)dosimetry and detector development. The minimum full aperture of the beamlines is approximately 100 mm at all magnetic elements, to accommodate the expected beam envelopes. Seven dipoles and twenty quadrupoles are needed for a total of 65 m of beamlines to provide the specified beams. In this paper we present the optical design for the three beamlines.